Konsep Dakwah Santri Di Era Disrupsi - Aris Priyanto; Mita Mahda Saputri (Jurnal Dakwah dan Komunikasi, 2022)
This research aims to explain the concept of santri da'wah in the era of disruption. The existence of the concept of da'wah for students in the era of disruption will determine the success of da'wah as an effort to symbolize Islam. Santri have a big role in creating a life order that is in accordance with the noble values contained in Pancasila and Islamic teachings. So that the concept of da'wah carried out is also expected to be on target and in accordance with current technological developments. This research is a qualitative research based on library research using descriptive analysis. The steps taken to obtain data began with collecting, documenting, reviewing and analyzing the various data found. This research seeks to reveal the concept of santri da'wah in the era of disruption, the characteristics of santri da'wah and the role of santri in da'wah in the era of disruption. Through this research, it was found that the concept of da'wah in the era of disruption was carried out by students by utilizing technological developments, the characteristics of students in preaching, and the role of students in the era of disruption in preaching.